REVIEW OF EARLY MARRIAGE ACCORDING TO CIVIL LAW AND THE IMPACT OF EARLY MARRIAGE ON INDONESIA - Allya Putri Yuliyani (Sean Institute, 2023)
The number of early marriages in Indonesia has decreased from the previous year, but the percentage of marriage dispensation applications to the religious court has increased in several regions in Indonesia. The phenomenon of early marriage in Indonesia is still a case of marriage which has a negative impact on Indonesia. According to the marriage law, the age limit for marriage is at least 19 years for both men and women, the marriage law has changed the age limit for marriage, which was originally 19 for men and 16 for women, this was done to suppress and prevent the occurrence of child marriages. Lack of quality human resources, loss of children's rights, occurrence of domestic violence are 3 of the many negative impacts of early marriage. In 2018 as many as 11.21% of women who had not yet reached the age of 19 had married, this made Indonesia the second most unfortunate country in ASEAN to have early marriages. The lack of outreach to children about the dangers of sex outside of marriage, economic difficulties, and a culture that is still thick with arranged marriages are 3 of the many factors that lead to early marriage. This study aims to provide information about the dangers of marrying young and how to prevent it. etc. It is hoped that through this research the community can care more and help the government in preventing early marriages.